Effect of ewe feeding on performance and meat quality of suckling lambs - D'Agata M.; Russo C.; Preziuso G.; Verità P. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
To compare the effect of pasture or total mixed ration (TMR) in the diet of Massese ewes on performance and meat quality of lambs, 20 suckling lambs were considered: 10 animals were given milk by ewes reared in pen and fed a TMR (group A), while 10 lambs were fed by mothers grazing pasture (group B); all the lambs were slaughtered at the typical commercial weight (14 kg). Carcasses were evaluated according to the Mediterranean grid, some linear measurements were taken on them and the right proximal pelvic limbs were dissected into the main tissue components. The longissimus lumborum muscle was instrumentally analysed in order to assess some meat quality characteristics. Lambs of the group A reached the target slaughtering weight four days before the lambs of group B (P=0.03) and tended to have higher carcass compactness. Carcass weight, state of fattening and meat colour were comparable between groups. Lambs of group B had a higher chest depth (P=0.01) and pelvic limb length (P=0.03), confirmed by a higher pelvic limb percentage (30.93% vs 24.39% respectively). No differences were revealed for histological dissection of pelvic limb and for organoleptic and chemical characteristics of meat. In conclusion, it seems that the rearing technique and ewes' nutrition can induce some modification in lambs' performance without any changes in the analysed characteristics of meat.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)